Complex treatment of experimental purulent wound of soft tissues - О. V. Lihonenko; О. V. Storozhenko; А. B. Zubakha; І. А. Shumeiko; І. О. Chorna (Клінічна хірургія, 2020)
Objective. To study the impact of estrogens and liposomes on course of healing process in purulent wounds of soft tissues in experiment.